Tex. A&M L. Rev. 2015
DOI: 10.37419/lr.v3.i2.4
|View full text |Cite
|
Sign up to set email alerts
|

“What Happened to Me Can Happen to Anybody”—Women Exonerees Speak Out

Abstract: Only a few studies have investigated the psychological consequences of wrongful conviction; several others have examined the psychological consequences of incarceration and its impact on reentry and reintegration, primarily for men. For women who have been wrongfully convicted and subsequently released from prison into the free world, there are further indignities and unique issues: having to deal with the deep personal loss of murdered loved ones along with criminal charges; the absence of DNA evidence, makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…These services should be provided immediately after release and should continue for as long as exonerees feel they need it. Researchers have also found that speaking about their experience helps some exonerees build confidence through acknowledgment and affirmation (Konvisser, 2015). As such, funding should be directed to organizations like Healing Justice, the Sunny Center, and others that are providing safe spaces for all those who are harmed by wrongful convictions.…”
Section: Discussion and Policy Considerationsmentioning
confidence: 99%
“…These services should be provided immediately after release and should continue for as long as exonerees feel they need it. Researchers have also found that speaking about their experience helps some exonerees build confidence through acknowledgment and affirmation (Konvisser, 2015). As such, funding should be directed to organizations like Healing Justice, the Sunny Center, and others that are providing safe spaces for all those who are harmed by wrongful convictions.…”
Section: Discussion and Policy Considerationsmentioning
confidence: 99%
“…31 It was particularly difficult for participants to regain their previous sense of self if they received no formal apology or public statement of innocence effectively 'delabelling' them. 33 One paper 34 noted positive changes in personality. Participants in this interview study noted that they had reflected on and grown from their experiences and reported changes such as a more positive attitude and not taking things for granted.…”
Section: Change In Self-identitymentioning
confidence: 99%
“…Symptoms of depression were also noted in several other studies. 34,35,37,[41][42][43][44] Anxiety. Anxiety and panic disorders also appeared to be common: 18/30 participants in the study reported by Burnett et al 27 and Hoyle et al 29 participants.…”
Section: Psychological and Physical Healthmentioning
confidence: 99%
See 2 more Smart Citations